Headmaster's Strategy to Improve the Quality of Teaching and Learning of Islamic Education in an Elementary School - Wyananda, Putri Azizah; Sulaiman, Sulaiman; Nurfadhilah, Nurfadhilah (International Journal of Islamic Studies Higher Education, 2022)
This research aims to analyze the strategies employed by school principals to enhance the quality of Islamic Religious Education in primary schools. The study utilizes a qualitative method with a case study approach. Data sources are obtained through structured interviews with four key informants, including the school principal, Islamic Religious Education teachers, homeroom teachers, and students. To strengthen the interview data, the author also conducts direct observations and analyzes relevant documentation to ensure comprehensive research outcomes. All data are analyzed using the Miles and Huberman data analysis techniques. The research findings reveal nine strategies implemented by school principals to improve the quality of instruction. These nine strategies consist of two aspects of planning (internal analysis and external analysis), five aspects of implementation (providing continuous motivation to teachers, enhancing teacher competence, fostering discipline among teachers and students, improving student quality, and enhancing learning facilities), and two aspects of evaluation (supervision and routine evaluation). These strategies can serve as references for schools in enhancing the quality of instruction in various primary schools in Indonesia